Post Office Savings Schemes-an Impetus for Rural Investment - Sakthi Srinivasan, K.; Lakshmi, S. Devi (Indian Journal of Marketing, 2006)
One of the most pressing concerns for the economies of the developing world is the need for mobilizing domestic financial resources. Despite the variety of vehicles that are intended to mobilize and allocate financial resources in developing countries, few offer strategies for meeting the needs of poor and lower-income people for financial services. Savings are increasingly being acknowledged as a powerful tool for poverty reduction. Postal savings funds play a significant role in financing public debt and in a number of countries the funds are intermediated through a variety of policy based financial institutions with developmental objectives, returning the funds to the direct benefit of the community of savers.